Dermatitis due to Mixed Demodex and Sarcoptes Mites in Dogs. (14th July 2014) - Sudhakara Reddy, B.; Nalini Kumari, K.; Sivajothi, S.; Venkatasivakumar, R.
Abstract : In dogs, dermatitis due to mixed mite infestation is rare. During the five-year period of study, two dogs were identified suffering from dermatitis due to mixed Demodex and Sarcoptes mites. Upon clinical examination dogs had primary and secondary skin lesions on face, around the ears, chin, neck, fore limbs and lateral abdomen. Microscopic examination of skin scrapings revealed Demodex and Sarcoptes mites. Both dogs were treated with daily oral ivermectin at 100 to 400 μ g/kg body weight as incremental doses, external application of amitraz and supportive treatments with topical antimicrobial shampoo. After completion of forty-two days of therapy, dogs were recovered from the dermatitis.